Semi-Automatic Generation of Assembly Instructions for Open Source Hardware - J.C. Mariscal-Melgar; Pieter Hijma; Manuel Moritz; Tobias Redlich (Journal of Open Hardware, 2023)
Documentation is an essential component of Open Source Hardware (OSH) projects both for co-development and replication of designs. However, creating documentation and keeping it up-to-date is often challenging and time-intensive. There are several systems that focus on this documentation challenge but they are limited in their support for keeping documentation up-to-date and relating CAD designs to documentation. This article proposes a semi-automated solution that relates the CAD design semantically to a textual specification from which we generate assembly instructions semi-automatically. Our system contains a CAD plugin and a compiler for the textual specification with which we show that we can replicate a state-of-the-art assembly manual to a high degree, that we can automate significant parts of the documentation process, and that our system can effectively adapt to documentation changes as a result of evolving designs. Our system leads to a methodology that we name “CAD-coupled documentation” integrating CAD design with the documentation process.